Fabrication of Thermoresponsive Hydrogel Scaffolds with Engineered Microscale Vasculatures. (22nd April 2021) - Li, Shuai; Wang, Wenhao; Li, Wentao; Xie, Mengfan; Deng, Changxu; Sun, Xin; Wang, Chengwei; Liu, Yang; Shi, Guohong; Xu, Yuanjing; Ma, Xiaojun; Wang, Jinwu
Abstract: Precise fabrication of microscale vasculatures (MSVs) has long been an unresolved challenge in tissue engineering. Currently, light‐assisted printing is the most common approach. However, this approach is often associated with an intricate fabrication process, high cost, and a requirement for specific photoresponsive materials. Here, thermoresponsive hydrogels are employed to induce volume shrinkage at 37 °C, which allows for MSV engineering without complex protocols. The thermoresponsive hydrogel consists of thermosensitive poly( N ‐isopropylacrylamide) and biocompatible gelatin methacrylate (GelMA). In cell culture, the thermoresponsive hydrogel exhibits an apparent volume shrinkage and effectively triggers the creation of MSVs with smaller size. The results show that a higher concentration of GelMA blocks the shrinkage, and the thermoresponsive hydrogel demonstrates different behaviors in water and air at 37 °C. The MSVs can be effectively fabricated using the sacrificial alginate fibers, and the minimum MSV diameter achieved is 50 µm. Human umbilical vein endothelial cells form endothelial monolayers in the MSVs. Osteosarcoma cells maintain high viability in the thermoresponsive hydrogel, and the in vivo experiment shows that the MSVs provide a site for the perfusion of host vessels. This technique may help in the development of a facile method for fabricating MSVs and demonstrates strong potential for clinical application in tissue regeneration. Abstract : A functional thermoresponsive hydrogel is used to induce volume shrinkage at 37 °C, which offers the possibility to fabricate smaller‐size microscale vasculatures. The volume shrinkage technique can produce vasculatures with a diameter less than 100 μm. In vitro and in vivo results demonstrate the biocompatibility of the hydrogel and the function of microscale vasculatures to bridge the host matrix.